The interaction and literary thought of Zhu Ziqing and Tschen Yin Koh A Study based on Zhu Ziqing\s Diary - Chan, Jye Yi (Tanjong Malim, 2022)
The interaction and literary thought of Zhu Ziqing and Tschen Yin Koh A Study based on Zhu Ziqing\s Diary by Chan, Jye Yi